ESTIMASI DAN TEST DIAGNOSA MODEL FUNGSI PERMINTAAN UANG DI INDONESIA - Nur Azizah (MediaTrend, 2006)
This research aimed to analyze empirical aspect of monetary phenomenon in Indonesia, especially related to demand for money. By using econometric model (liniar, logarithmic and partial adjusted model), function of demand for money has been estimted with approach of Ordinary Least Squares, Two Stage Least Squares and Generalized Instrumental Variables Estimator (GIVE). Results of research indicate that Partial Adjusted Model (PAM) with have been estimated by GIVE relative superior compared to linear and logarithmic model. Farther, in short run income elasticity of demand for money is inelastic though on a long term will become very elastic. Meanwhile, influence of interest rate to demand for money is not significant in conventional level (5%). This fact cannot be discharged from condition of economic crisis since mid 1997.